When Sustainability Backfires: A Dual-Path Model of Trust Erosion and Consumer Skepticism in Green Marketing - Najmudin, Mohamad; Helmi, Sulaiman; Tamamudin; Rifqi, Husni Muhammad (Universitas Brawijaya, Indonesia, 2025)
The rapid expansion of sustainability marketing has increased the risk of greenwashing, raising urgent concerns about declining consumer trust and the effectiveness of environmental communication. As consumers become more environmentally aware, misleading green claims may not only fail to persuade but also actively undermine pro-environmental purchasing behavior. This study aims to examine how perceived greenwashing influences purchase intention by analyzing the mediating roles of consumer skepticism and brand trust, as well as the moderating role of environmental concern. Employing a quantitative, cross-sectional research design, data were collected through an online questionnaire from 340 adult consumers who had been exposed to environmental marketing claims. A purposive sampling technique was applied to ensure respondent relevance, and the data were analyzed using Partial Least Squares Structural Equation Modeling. The results demonstrate that perceived greenwashing significantly increases consumer skepticism and reduces brand trust, both of which mediate its negative effect on purchase intention. In addition, environmental concern strengthens these relationships, indicating that environmentally concerned consumers react more strongly to perceived inconsistencies in green claims. This study offers novelty by integrating signaling theory and attribution theory into a consumer-centric dual mediation model that explains why sustainability messaging can backfire when credibility is questioned. The findings provide important implications for marketers and policymakers by highlighting the need for credible, verifiable environmental communication and stronger governance of green marketing practices.